THE PORTRAIT OF MAN AND SOCIETY IN THE WIND-TITLE WORKS (Scientific journal of the Fergana State University, 2026)
The article examines the role of the author's choice of details characteristic of the depiction of a landscape as the title of a work of art in revealing its symbolic and ideological meaning. In this regard, a comparative analysis of works of Uzbek and world literature is carried out. The authors' mastery in using the detail of wind as a title is studied.